Electronic Shopping a Paradigm Shift in Buying Behaviour Among Indian Consumers - Agarwal, Varsha (Korea Review of International Studies, 2022)
Recent in the realm of e-business, electronic shopping is unquestionably the way of the future for consumers everywhere. Nearly every business nowadays has an online storefront where customers may purchase goods and services. Despite the fact that online shopping is quite prevalent in countries outside of India, its rise in the Indian Market, a sizable and strategically important consumer market, is still in line with the worldwide market. The notion to investigate the current state of online purchasing in India was prompted by the sector's apparent future expansion. The internet's proliferation has led to a sea change in established practices. Customers' information-gathering practices have been revolutionized by the Internet and the global web (www). The Internet was conceived of as a means of information pursuit the online world plays a crucial role in the global economy. The results of the online study might help shops understand the expectations of online customers and the factors that influence their behavior. The study concluded that to formulate and implement their e-business strongly efficiently and effectively and possess a stronger competitive advantage, businesses must first gain an understanding of the key drivers that could have an impact on the attitudes of online consumers toward the products and services they offer.
ISME
Keywords: Consumer Perception; Online Shopping; and consumer purchasing behaviour